Global Chinese Pentecostal and Charismatic Christianity - Yang, Fenggang. (Global Pentecostal and Charismatic Studies, 2017)
This is the first scholarly volume on Chinese Christian Pentecostal and charismatic movements around the globe. The authors include the most active and renowned scholars of global Pentecostalism and Chinese Christianity, including Allan Anderson, Daniel Bays, Kim-twang Chan, Gordon Melton, Donald Miller, and Fenggang Yang. It covers historical linkages between Pentecostal missions and indigenous movements in greater China, contemporary charismatic congregations in China, Singapore, Malaysia, and the United States, and the Catholic charismatic renewal movement in China. The volume also engages discussion and disagreement on whether it is even appropriate to refer to many of the Chinese Christian movements as Pentecostal or charismatic. If not, are they primarily following cultural traditions, or upholding beliefs and practices in the Bible? Contributors are: Allan H. Anderson, Connie Au, Daniel H. Bays, Michel Chambon, Kim-kwong Chan, Weng Kit Cheong, Jiayin Hu, Ke-hsien Huang, Melissa Wei-Tsing Inouye, Karrie J. Koesel, Yi Liu, J. Gordon Melton, Donald E. Miller, Selena Y.Z. Su, Joy K.C. Tong, Yen-zen Tsai, Fenggang Yang, Rachel Xiaohong Zhu.